(untitled) (Research, Society and Development, 2020)
This work is an exploratory study with the objective of mapping and interpreting some Teachers Representations on Science and Scientific Education. With a qualitative approach, through interviews, it was made a research with some teachers of Natural Sciences from a Public Educational Institution in the Midwest of Minas Gerais. The methodology used in the interpretation of the data collected was Content Analysis. Although it is an exploratory study, the result of the research indicates that the renewal in Science Education needs to occur based on reflections on questions of epistemology because these guide the understanding of scientific practice and Science Teaching.